Bromine, iodine and sodium along the EAIIST traverse: Bulk and surface snow latitudinal variability - Celli G.; Cairns W. R. L.; Scarchilli C.; Cuevas C. A.; Saiz-Lopez A.; Savarino J.; Stenni B.; Frezzotti M.; Becagli S.; Delmonte B.; Angot H.; Fernandez R. P.; et al. (Environmental Research, 2023)
During the East Antarctic International Ice Sheet Traverse (Eaiist, december 2019), in an unexplored part of the East Antarctic Plateau, snow samples were collected to expand our knowledge of the latitudinal variability of iodine, bromine and sodium as well as their relation in connection with emission processes and photochemical activation in this unexplored area. A total of 32 surface (0–5 cm) and 32 bulk (average of 1 m depth) samples were taken and analysed by Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Our results show that there is no relevant latitudinal trend for bromine and sodium. For bromine they also show that it has no significant post-depositional mechanisms while its inland surface snow concentration is influenced by spring coastal bromine explosions. Iodine concentrations are several orders of magnitude lower than bromine and sodium and they show a decreasing trend in the surface samples concentration moving southward. This suggests that other processes affect its accumulation in surface snow, probably related to the radial reduction in the ozone layer moving towards central Antarctica. Even though all iodine, bromine and sodium present similar long-range transport from the dominant coastal Antarctic sources, the annual seasonal cycle of the ozone hole over Antarctica increases the amount of UV radiation (in the 280–320 nm range) reaching the surface, thereby affecting the surface snow photoactivation of iodine. A comparison between the bulk and surface samples supports the conclusion that iodine undergoes spring and summer snow recycling that increases its atmospheric lifetime, while it tends to accumulate during the winter months when photochemistry ceases.